Oxide Transistors: Metal Oxide Transistors via Polyethylenimine Doping of the Channel Layer: Interplay of Doping, Microstructure, and Charge Transport (Adv. Funct. Mater. 34/2016). (12th September 2016) - Huang, Wei; Zeng, Li; Yu, Xinge; Guo, Peijun; Wang, Binghao; Ma, Qing; Chang, Robert P. H.; Yu, Junsheng; Bedzyk, Michael J.; Marks, Tobin J.; Facchetti, Antonio
Abstract : Enhanced metal oxide (In2 O3, IZO, IGZO) transistor performance via polyethylenimine (PEI) doping is demonstrated by J. Yu, M. J. Bedzyk, T. J. Marks, A. Fachetti, and co‐workers on page 6179. PEI electron donating capacity combined with charge trapping and variation in the matrix film microstructure contribute, for proper PEI doping levels, to high electron mobility, optimal TFT off‐currents, and optimal threshold voltages. This concept is promising for opto‐electronic devices based on metal oxide films.